Empowerment of Youth Red Cross (PMR) Members in First Aid Practices for Managing Fainting Cases at SMK Ahmad Yani Gurah: Pemberdayaan Anggota PMR Dalam Praktek Pertolongan Pertama Pingsan Di Smk Ahmad Yani Gurah - heni, heni (Bhakti Sabha Nusantara, 2026)
Background: Fainting (syncope) is a common emergency in school settings, particularly during ceremonies and physical activities. Members of the Youth Red Cross (Palang Merah Remaja/PMR) are expected to possess adequate first aid skills to respond promptly and appropriately to fainting incidents in accordance with established Standard Operating Procedures (SOPs).Methods: This community service activity consisted of health education sessions and hands-on first aid practice using instructional media. The program was conducted at the Hall of SMK Ahmad Yani Gurah from October 20 to November 20, 2025. A total of 39 PMR students and 6 university students participated. Participants’ first aid skills were evaluated using pre-test and post-test observation sheets.Results: Pre-test results showed that nearly half of the participants (17 students; 43.6%) achieved a score of 60, indicating limited initial competence. Post-test results demonstrated a substantial improvement, with most participants (30 students; 76.9%) achieving scores above 88, reflecting enhanced first aid skills in managing fainting cases.Conclusion: First aid training for fainting management significantly improved the competence of PMR members. Continuous and structured training programs, both within and outside school settings, are recommended to ensure adherence to SOPs and to promote active participant engagement. Keywords: Youth Red Cross Empowerment; First Aid; Fainting (Syncope); Vocational High School; SMK Ahmad Yani Gurah